(untitled) (Research, Society and Development, 2020)
Cell phones are essential objects in everyday life and their frequent use in contaminated places generates a focus for pathogenic bacteria that cause nosocomial infections. This suggests that mobile devices have the potential to be a source of the spread of several microorganisms. The objective of this article is to evaluate the presence of bacteria in cell phones of health professionals and academics at a college located in the Southwest of Goiás. This is a quantitative cross-sectional study carried out from February to May 2019. 107 samples of cell phones were collected, from 19 health professionals and the rest from dentistry and medicine students. It was observed that more than 75% of those evaluated use their cell phones simultaneously with the attendance and report that they have never performed asepsis on their devices. It found that 95.28% of the cell phones were contaminated, 88.67% of the gram positive group. It is noted that the hygiene of cell phones and hands is essential to reduce the spread of microorganisms that cause nosocomial infections. It is important to asepsis the cell phone at least three times a week with 70% alcohol to prevent it from being a vehicle for pathogenic bacteria.